1998
DOI: 10.1111/j.1095-8649.1998.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Detritivory in two Amazonian fish species

Abstract: In floodplain lakes of Central Amazon, the siluriform Liposarcus pardalis and the characiform Prochilodus nigricans consumed detritus with different compositions. Most of the diet of L. pardalis and P. nigricans was made of amorphous organic matter. The food ingested by L. pardalis had relatively higher organic matter (OM) (35-55%) and crude protein (10-19%) than that found in P. nigricans stomachs (10-20% and 2-5%, respectively). Both fish ingested higher quantities of OM and crude protein during the high-wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
1
14
2
1
Order By: Relevance
“…This is a food originated from different sources of carbon (cellulose, lignin, chitin and other) and presents particles of variable size, colonized in different degrees by fungi and bacteria, its main source of protein (Bowen, 1979;Yossa & Araujo-Lima, 1998;Crossman et al, 2001;Moore et al, 2004). In this context, it is possible to cogitate the occurrence in Alagados Reservoir of detritus qualitatively improved.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is a food originated from different sources of carbon (cellulose, lignin, chitin and other) and presents particles of variable size, colonized in different degrees by fungi and bacteria, its main source of protein (Bowen, 1979;Yossa & Araujo-Lima, 1998;Crossman et al, 2001;Moore et al, 2004). In this context, it is possible to cogitate the occurrence in Alagados Reservoir of detritus qualitatively improved.…”
Section: Discussionmentioning
confidence: 97%
“…This fact could be justified by the low biomass of periphytics algae in Alagados Reservoir (Rodrigues et al, 2005) and the intrinsic link of benthic algae to non live detritus/sediment extract (Bowen, 1983;Gerking, 1994;Yossa & Araujo-Lima, 1998;Crossman et al, 2001;Moore et al, 2004). Occurrences of algae in the diet of A. paranae were also reported for stream populations (Ferreira, 2004), however, the absence or inexpressive consumption of detritus/ sediment indicated, in these cases, the intentional ingestion of this food.…”
Section: Discussionmentioning
confidence: 99%
“…Diet, energy sources and food assimilation of black prochilodus have been widely studied through direct analyses of the stomach contents, fat storage and analyses of stable carbon isotopes by several authors (Goulding, 1981;Junk, 1985;Araujo-Lima et al, Yossa, Araujo-Lima, 1998Goulding, 1981Junk, 1985;). Although visual assessment of stomach fullness of black prochilodus in the Aguarico River was qualitative, it showed a decrease in feeding activity during migrations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy that allows such efficiency is the ability to ingest large quantities of food in relation to body weight (Yossa & Araújo-Lima 1998). The fact that there were discrepancies in energy, protein, and ADC contents for P. lineatus may be related to the quantity of ingested food because the diet of P. lineatus is mainly composed of detritus and sediment (Table 1) (Hahn et al 2002).…”
Section: Prochilodus Lineatusmentioning
confidence: 99%
“…Nose (1966) reports that, in general, protein is adequately digested by most fish species, except for a few plant protein sources or in the presence of high levels of carbohydrates in the diet. Few studies have been developed in Brazil with this focus in natural environments (Yossa & Araújo-Lima 1998, Silva et al 2000. Some research has shown that the effective assimilation of food by fish depends also on the hydrological regime, environmental condition, water temperature, food intake, and nutrient quantity and quality, as well as the physical state of food items (Silva et al 2000).…”
mentioning
confidence: 99%